Archaeological Survey of the Relics of Early Modern Manor Complexes in Kozłów, in the Region of Upper Silesia - Radosław Zdaniewicz; Monika Michnik (Fasciculi Archaeologiae Historicae)
Archaeological surveys of the relics of the motte-and-bailey manor in Kozłów in Upper Silesia (Poland) have yielded a great deal of interesting information regarding the life of nobility around that area in early modern times. Apart from relics of manor houses dating back to various periods, a number of artefacts has been found as well. Particularly noteworthy is a set of Renaissance tiles as well as tools and other iron items comprising the furnishings of the 16th/17th-century manor house. These are indicative of the social and material status of its inhabitants.